Bilateral deficit and bilateral performance: Relationship with sprinting and change of direction in elite youth soccer players - Ascenzi, G.; Ruscello, B.; Filetti, C.; Bonanno, D.; Di Salvo, V.; Nuñez, J.; Mendez-Villanueva, A.; Suarez-Arrones, L. (Sports, 2020)
The purpose of the study was to examine the differences in bilateral deficit (BLD) at different loadings during the half-squat jump (SJ) and horizontal countermovement jump (HCMJ) to determine if there is a relationship with linear sprint or change of direction (COD). The second goal was to check if fast players were more powerful in SJ and HCMJ than slow players in bilateral performance (BP). Twenty-seven male youth soccer players participated in the study. Players were divided in two groups, faster and slower, according to their sprint performance (10 and 40 m). BLD average power with body weight (BW) and 25%BW were significantly higher than 50%BW (p < 0.01). BLD during HCMJ was significantly higher than BLD during SJ with BW, 25%BW and 50%BW (p < 0.01). There were no statistical relationships between BLD and sprint or COD performance (p > 0.05). Fast players showed significantly higher SJ power with all the different loads and HCMJ than slow players (p < 0.01), and fast players lost more time executing COD-90° than slow players (p < 0.01). There were no statistical differences between fast and slow players in BLD. BLD seems to be dependent on motor task, contraction type and load and could not be a proper measure to estimate sprint and COD performance. Faster players are confirmed to be more powerful players than slow players, and decrements in COD could be a key benchmark to identify deficit between linear and COD performance.